O discurso falso no Sofista de Platão - Souza, Luiz Claudio Nogueira de (2017)
The objective of this study is to examine the false speech in the Plato's Sophist, assuming that there are both an ontological and an ethic-political aspect related to the platonic thesis sketched in The Sophist, according to which it´s possible to make false statements. It´s sought through the direct reading of the text to analyse the theme of the possibility of speech and, specifically, the false speech in The Sophist, considering not only its logic-grammatical structure but also the intelligible reality of the communion of forms and, above all, the technique in the making of speech as a way of action and interaction among men in the core of the city. The hypothesis is that Plato shows the possibility of false speech from the communion of forms and the logic-grammatical structure in the speech, but doesn´t seek to establish any logical criteria or objective that allows a direct and immediate distinction between true and false speech. Under this assumption what follows is that the ethic-political aspect of the speech, evinced through the mimetic art, becomes essential for a possible distinction between true and false speech.